PENERAPAN CRADLE HOLD POSITION TERHADAP PENINGKATAN PERLEKATAN BAYI PADA ASUHAN KEPERAWATAN IBU POST SECTIO CAESAREA (SC) DI RS TK. II. 03. 05. 01 DUSTIRA TANGGAL 22-24 MEI 2025 - Wahyuni, Sri; Ati Nurhayati, Nung; Darmayanti (Yayasan Putra Sukamanah Sejahtera, 2025)
Exclusive breastfeeding globally has only reached 48%, shy of the 2025 target of 50%. In Indonesia, 1 in 5 newborns is given food other than breast milk within first 3 days of life. One contributing factor to the failure of exclusive breastfeeding is poor latch-on. Inadequate breastfeeding can lead to risks such as malnutrition, childhood diabetes/obesity, lower cognitive development, and a higher risk of infection due to insufficient immunoprotection. Improper latch can also worsen mother condition like nipple trauma and psychological distress due to pain. This case study aims to implement nursing care for a post-SC mother, with a focused intervention on improving the baby's latch using the cradle hold position. The intervention was carried out over 3 days, during a single breastfeeding session each day. The case study revealed an improvement in the LATCH score from 7 (adequate) on the first day, to 8 (good) on the second day, and 10 (excellent) on the third day. Additionally, the mother reported increased confidence in breastfeeding, reduced pain and more optimal post-surgery recovery. Cradle hold position proved effective in enhancing infant latch and supporting successful breastfeeding of post-SC mother. The author recommends integration of breastfeeding education into health services, particularly at Dustira Hospital to prevent lactation issues and help ensure more successful exclusive breastfeeding programs.